New information on the etiology and biological targets of wounds associated with diabetes - Ghosh, Niladry S.; Dubey, Anubhav; Kumari, Mamta (Creative Pharma Assent, 2025)
Background: Wound healing is a complex process that advances through inflammation, proliferation, and remodelling phases. Diabetes precipitates numerous ailments that obstruct practically all of these reparative processes. Methodology: We performed a literature search on ScienceDirect and PubMed databases using various keywords, including